Wine science principles and applications - Jackson, Ron S. (Elsevier/Academic Press, 2008)
Understand the three pillars of wine science---- grape culture, wine production, and sensory evaluation-- in the third edition of this bestselling title. Author Ronald Jackson takes readers on a scientific tour into the world of wine by detailing the latest discoveries in this exciting industry. From grape anatomy to wine and health, this book includes coverage of material not found in other enology or viticulture texts including details on cork and oak, specialized wine making procedures, and historical origins of procedures. Jackson uniquely breaks down sophisticated techniques, allowing the reader to easily understand wine science processes. NEW to this edition: * Extensive revision and additions on: chemistry of red wine color, origin of grape varietyies, wine language, significance of color and other biasing factors to wine perception, various meanings and significance of wine oxidation * Significant additional coverage on brandy and ice wine production * New illustrations and color photos.
Previous ed.: 2000.
Keywords: víno; vinařství; výroba vína; vinohradnictví; wine; wine making; viticulture; monografie; elektronické knihy; monographs; electronic books